The Effect of Service Quality in the Involvement of Participants in Leisure Dance Activity - SAVVIDOU, Kyriaki; GOULIMARIS, Dimitris; KOSTA, George; BEBETSOS, Eyaggelos; TSITSKARI, Efi (Journal of Environmental Management and Tourism; Vol 12 No 8 (2021): JEMT, Volume XII, Issue 8(56), Winter 2021, 2021)
Involving in leisure activities becomes important since it contributes to a better use of leisure time, socialization, entertainment and improvement of the quality of personal life. The aim of this study was to investigate the differentiation of the involvement factors (attractiveness, centrality and self-expression) concerning people who participate in dance activities, after the application of an intervention program on the services provided by the cultural organizations teaching Greek dances. The participants were adults (N = 384), aged 18 to 67 years. The evaluation of the participants' involvement was carried out with the use of a questionnaire by Kyle, Graefe, Manning and Bacon (2003). To carry out the research, two measurements were made before and after the intervention program in order to evaluate the participants’ involvement in relation to the services provided by dance organizations. The results of the study showed that the proposals and activities designed to improve the services provided by the managers of the cultural organizations that participated in the intervention program, increased the involvement factors. In conclusion, the degree of involvement of those who participate in Greek dances activities can increase, when the services provided are of high quality.